A study on influence tactics and job promotion amongst administrative staff / Nur Farhana Ab Ghani and Nurfarahin Yusof - Ab Ghani, Nur Farhana Ab.Ghani; Yusof, Nurfarahin (Faculty of Administrative Science and Policy Studies, 2013)
Kacmar & Carison (1997) perceived organizational politics as social influence attempts directed at those who can provide rewards that will help to promote or protect their self interests of the actor. Besides, it also can be defined as the processes, the actions, the behaviors through which potential power is utilized and realized (Pfeffer,1992). In relation to the above definition, Dubrin (2001) stated that organizational politics known as informal approaches to gain power through various tactic other than merit or luck. Therefore, it can be concluded that organizational politics is the approach used by an employee in order to gain power and better positions.